Pengaruh Efektivitas Dana BOS terhadap Standar Nasional Pendidikan melalui Kepemimpinan Kepala Sekolah dan Partisipasi Warga Sekolah di SMK Kota Kupang - Sanam, Ayub Simon Petrus; Wulakada, Hamza H.; Nalle, Agus (Indonesian Journal of Teaching and Teacher Education, 2025)
This study aims to analyze the effectiveness of the utilization of School Operational Assistance Funds (BOS) on the achievement of National Education Standards (SNP) through the mediating role of principal leadership and school community participation in Vocational High Schools (SMK) in Kupang City. The study used a quantitative approach with a survey method. The research sample consisted of 198 respondents from 21 SMK in Kupang City and were selected using a stratified sampling technique. Data were collected through a structured questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results showed that the effectiveness of BOS Funds significantly influenced the achievement of SNP with a total effect of 0.77 (p<0.001), consisting of a direct effect of 0.38 and an indirect effect through principal leadership (0.21) and school community participation (0.18). The research model was able to explain 63% of the variation in SNP achievement. These findings confirm that optimizing BOS Funds requires effective principal leadership and active participation of school community so that the utilization of funds has a maximum impact on improving the quality of vocational education.